BEHAVIOUR THEORY OF THE FIRM – ALTERNATIVE OF THE NTOCLASSICAL ORTHODOXY - Давыдова, И. А. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
The author considers one of wide spread in the modern economic science current of the theory of the firm, which studies procedures of acceptance of decisions be economic subjects in the different situations. It is considered the possibilities to use deductions of the behavior theory of the firm in transformer economy.